1999
DOI: 10.2807/esm.04.06.00056-en
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of calicivirus gastroenteritis associated with eating frozen raspberries

Abstract: Small round structured viruses (SRSVs - for example, calici-, astro-, and entero-viruses) are the commonest causes of outbreaks of non-bacterial gastroenteritis worldwide. Transmission of SRSVs by water and by various foods – including salads, bakery prod

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
25
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 8 publications
0
25
0
Order By: Relevance
“…Transmission of viruses associated with the consumption of contaminated bivalve shellfish, particularly, oysters which are eaten uncooked, is regularly reported (Koopmans and Duizer 2004;Widdowson et al 2005). Other foods, including raspberries (Cotterelle et al 2005;Le Guyader et al 2004;Gaulin et al 1999;Korsager et al 2005;Hedlund et al 2000;Falkenhorst et al 2005;Hjertqvist et al 2006;Fell et al 2007;Ponka et al 1999) and salads (Vivancos et al 2009), have caused outbreaks after being contaminated by polluted water or virus-infected food handlers. Polluted water, both drinking water and recreational water, have been shown to have transmitted viruses (Cannon et al 1991;Lawson et al 1991;Maunula et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Transmission of viruses associated with the consumption of contaminated bivalve shellfish, particularly, oysters which are eaten uncooked, is regularly reported (Koopmans and Duizer 2004;Widdowson et al 2005). Other foods, including raspberries (Cotterelle et al 2005;Le Guyader et al 2004;Gaulin et al 1999;Korsager et al 2005;Hedlund et al 2000;Falkenhorst et al 2005;Hjertqvist et al 2006;Fell et al 2007;Ponka et al 1999) and salads (Vivancos et al 2009), have caused outbreaks after being contaminated by polluted water or virus-infected food handlers. Polluted water, both drinking water and recreational water, have been shown to have transmitted viruses (Cannon et al 1991;Lawson et al 1991;Maunula et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological investigations of outbreaks have shown that the most important modes of transmission are person-to-person contacts and contaminated food and water (20,31). Multistate and global outbreaks linked to the distribution of contaminated foods and water have been reported (4,6,14,45). Moreover, the emergence of a common strain with global distribution has raised important questions on the likelihood of massive food-borne introduction of new NLV strains (43,51).…”
mentioning
confidence: 99%
“…They are transmitted both directly, via person-to-person contact, and indirectly by environmental contamination (31), via foods and drinking water (5,13,21,22,28,32,36,37). The number of cases which can be attributed to food-or waterborne transmission is not known exactly (10).…”
mentioning
confidence: 99%